2016
DOI: 10.1097/fjc.0000000000000340
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Properties of a Novel Morphologic Derivative (4-tert-buthyl-2,6-bis(thiomorpholine-4-ilmethyl)phenol)

Abstract: We evaluated the antihypertensive properties of 4-tert-buthyl-2,6-bis(thiomorpholine-4-ilmethyl)phenol (TBTIF). Spontaneously hypertensive rats were treated with TBTIF or captopril (both at 1 mg·kg⁻¹·d⁻¹ intramuscularly for 4 days), and their blood pressure (BP) was assessed. In some experiments, concentration response curves to angiotensin I or angiotensin II were generated in rat aortic rings and in the absence or presence of Ang-(1-7), N(G)-monomethyl L-arginine, or both; additionally, the angiotensin-conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“… 18 The antihypertensive therapy could reverse these changes. 19 In this sense, it has been seen that ACEI as captopril or a new thiomorpholine compound decreases ACE messenger RNA and reactivity of Ang-II in SHR to levels obtained in normotensive rat; 20 propranolol treatment reduces the renin 21 and ACE levels in infantile hemangioma; 22 losartan, an ARA, attenuates cardiac oxidative stress induced by Ang-II. 23 According to these evidence, our data obtained corroborated the results mentioned above, due to the fact that captopril, losartan, and propranolol reduced the BP values ( Table 1 ) and Ang-II induced reactivity only with the 2 first while propranolol increased it ( Figures 1 and 2 ).…”
Section: Discussionmentioning
confidence: 99%
“… 18 The antihypertensive therapy could reverse these changes. 19 In this sense, it has been seen that ACEI as captopril or a new thiomorpholine compound decreases ACE messenger RNA and reactivity of Ang-II in SHR to levels obtained in normotensive rat; 20 propranolol treatment reduces the renin 21 and ACE levels in infantile hemangioma; 22 losartan, an ARA, attenuates cardiac oxidative stress induced by Ang-II. 23 According to these evidence, our data obtained corroborated the results mentioned above, due to the fact that captopril, losartan, and propranolol reduced the BP values ( Table 1 ) and Ang-II induced reactivity only with the 2 first while propranolol increased it ( Figures 1 and 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In SHRs, one experiment showed that aortic ACE2 mRNA was within the no/marginal change level and was unaffected by captopril [88], whereas another revealed aortic mRNA overexpression, with reversal to the repression level by losartan or to the no/marginal change level by captopril (Fig. 4A) [89].…”
Section: Hypertensionmentioning
confidence: 98%
“…The reactions of maleimides with the involvement of 1,4-N,O-binucleophiles also proceed in a similar way. During these transformations, unsaturated oxazine (morpholine) cycles are formed, which are part of a number of compounds with a wide spectrum of biological activity [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. A. V. Zorina et al [67,68] studied the interaction of 1 with aminophenol 55 and aminoethanols 56 in detail.…”
Section: Reactions With S-and O-containing Dinucleophilesmentioning
confidence: 99%